Mekanisme Perlindungan Korban Kekerasan Seksual Pondok Pesantren Yayasan Manarul Huda Bandung - Gita Raudhah R.A; Muliasa Insani Candra; Qurratu Aini Aprilia; David Nugraha Saputra (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to explore the protection mechanisms for victims of sexual violence in Islamic boarding schools, with a special focus on the tragic case that occurred at the Yayasan Manarul Huda Islamic Boarding School in Bandung. Between 2016 and 2021, 13 female students were victims of sexual violence by the boarding school owner, and nine of them gave birth to children. This case highlights the weakness of the protection system in Islamic boarding schools and the imbalance in power relations between kyai and students. This study uses a qualitative approach through a literature study method to analyze legal documents, journals, and relevant reports related to child protection and sexual violence in religious educational institutions. The results of the study indicate that the main factors that exacerbate the situation are the lack of a safe reporting mechanism, the lack of technical regulations governing child protection in Islamic boarding schools, and a patriarchal culture that silences the voices of victims. This study also found the importance of the involvement of families, communities, and state institutions in building a preventive, responsive, and curative child protection system. Recommendations include the formation of internal policies in Islamic boarding schools, the establishment of a child protection task force, and active cooperation with external institutions such as the Ministry of Religion and the Indonesian Child Protection Commission. A confidential reporting system and regular training are needed for all parties in the Islamic boarding school to create a safe and dignified learning environment.